Micronised biomass silica as cement replacement material in concrete. - Adnan, Suraya Hani
Micronised Biomass Silica (MBS) is an agricultural waste product which comprises of high content of silica. This study was conducted on the off-white amorphous biomass silica ash derived from the rice husk with pozzolanic index 69%. Various percentages of MBS ranging from 0% to 20% by mass have been used as cement replacement material. Compressive strength and water permeability of concrete with MBS incorporation were investigated. From the results obtained, it was identified that up to 12% of MBS is able to produce concrete with higher strength and lower in water permeability compared to control concrete.